The aerodynamic behaviour of a compressor rotor with steady and unsteady inlet flow - Overli, J. M. (Cranfield University, 1974)
Recent developments in have made possible the mic behaviour of rotor stage compressor using I pressure sensing and transfer techniques detailed investigation of the aerodyna- blades. Tests on a low speed single this instrumentation have given new evidence on rotor behaviour. The rotor blade performance with steady inlet flow condition was assessed from surveys of total pressure, static pressure and flow direction made upstream and downstreäm of the rotor hub, mid-height and tip section. In addition, measurements of the static pressure distributions of the same blade sections were completed. It is concluded that the combined effect of centrifugal force and annulus wall boundary layer skewing aid the performance of the rotor. This suggests that the efficiency of compressors would be improved if they were designed for reactions of rather more than 50%. The presence of a tip shroud has the effect of enhancing the overall compressor performance. A comparison of compressor rotor and two-dimensional cascade blade results is given, and predictions of the boundary layer development and the pressure distribution around the blades under various flow conditions are also presented. A series of experiments were also conducted at the mid-height section in which the compressor was subjected to 'sine-wave' and 'square-wave' circumferential stagnation pressure distortions including tests with the compressor operating in the surge regime. The deteriorating effect of total pressure distortion on overall compressor performance is clearly demonstrated, and a critical sector of spoiling is found. The effect of the level of reduced frequency on the unsteady normal force response of rotor blades is shown. II In all cases of distorted inlet flow, stallwinception is dela ed until values of normal force coefficient are reached well in excess of those encountered at steady state maximum. For 'square-wave' type distortion this is ensued by a complex stall situation with separation bubbles apparently traversing the rotor blade section and promoting dynamic lift patterns which pass through secondary and tertiary peaks. One may conclude that the aerodynamic rotor behaviour in the presence of such an unsteady flow environment is not predictable by current mathematical models. A theoretical analysis of the transient flow applicable at low values of reduced frequency is given. The transient response of the pressure-transmitting system was examined thoroughly theoretically, and experimental frequency response tests were conducted on the rotor blades as well as on a subsidiary rig. Careful examination of the fluctuating pressure signal was performed including time and frequency analyses.